The Impact of Training Indigenous Facilitators for a Two-Eyed Seeing Research Treatment Intervention for Intergenerational Trauma and Addiction - Marsh, Teresa Naseba; Marsh, David C.; Najavits, Lisa M. (The International Indigenous Policy Journal, 2020)
Intergenerational trauma in Indigenous Peoples was not the result of a targeted event, but rather political and governmental policies inflicted upon entire generations. The resultant effects of these traumas and multiple losses include addiction, depression, anxiety, violence, self-destructive behaviors, and suicide, to name but a few. Traditional healers, Elders, and Indigenous facilitators agree that the reclamation of traditional healing practices combined with conventional interventions could be effective in addressing intergenerational trauma and substance use disorders. Recent research has shown that the blending of Indigenous traditional healing practices and the Western treatment model Seeking Safety resulted in a reduction of intergenerational trauma (IGT) symptoms and substance use disorders (SUD). This article focuses on the Indigenous facilitators who were recruited and trained to conduct the sharing circles as part of the research effort. We describe the six-day training, which focused on the implementation of the Indigenous Healing and Seeking Safety model, as well as the impact the training had on the facilitators. Through the viewpoints and voices of the facilitators, we explore the growth and changes the training brought about for them, as well as their perception of how their changes impacted their clients.